2011
DOI: 10.4187/respcare.00851
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Reliability of Extubation Decisions by Intensivists

Abstract: BACKGROUND: Mortality increases when extubations fail. Although predictors of extubation failure have been evaluated, physicians' reasoning to extubate a patient has received minimal attention. We hypothesized that the accuracy and reliability of physicians' extubation decisions are low. METHODS: We sent surveys to 55 physicians in the divisions of pulmonary and critical care medicine of 3 teaching hospitals in Chicago, Illinois. The survey comprised 32 clinical vignettes of real patients who were extubated af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Another way for ICU healthcare workers to determine the amount of airway secretions is the frequency of tracheal suctioning. It has been reported that intensivists use lower levels of airway secretion as an adjunctive indicator of successful extubation [ 14 , 19 ]. In this study, the frequency of tracheal suctioning was associated with reintubation.…”
Section: Discussionmentioning
confidence: 99%
“…Another way for ICU healthcare workers to determine the amount of airway secretions is the frequency of tracheal suctioning. It has been reported that intensivists use lower levels of airway secretion as an adjunctive indicator of successful extubation [ 14 , 19 ]. In this study, the frequency of tracheal suctioning was associated with reintubation.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, although moderate to copious tracheal secretions predict extubation failure, 27,28 only a few physicians rely on the amount of secretions as an extubation readiness parameter. 29 Quantifying secretions is difficult. Secretions can be assessed semi-quantitatively based on the required frequency of suctioning: once every 2-4 hours, once every 1-2 hours, or several times per hour.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred five studies of 657 articles (16%) identified by date and keywords criteria search met inclusion criteria for analysis (Fig. 1) (2, 13–116) and were published in 55 different journals ( Supplemental Table 4 , http://links.lww.com/CCM/H371). Notably, 70 (67%) of the included studies were published in only four journals ( Critical Care Medicine , Journal of Critical Care , Journal of Intensive Care , and Neurocritical Care ).…”
Section: Resultsmentioning
confidence: 99%